Peran Badan Pertanahan Nasional Dalam Mengoptimalisasi Penyelesaian Konflik Lahan Desa Maroangin Kecamatan Maiwa Kabupaten Enrekang - Sukran, Sukran; Parawangi, Anwar; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2021)
This study purposed to find out how the position and the National Land Agency of Enrekang Regency work together with the local government of Enrekang Regency in optimizing conflict resolution. This study used qualitative methods carried out by collecting data through library research, field research in the form of observations, in-depth interviews and document research. The results of this study showed that the role of the Enrekang Regency National Land Agency had been proceeding, it could be seen from the regulator's point of view actually arranging to find out the clarity of the conflict that occurred between PT. PN XIV and the community of Maroangin Village, Maiwa sub-district, aspects of the dynamics of the government both sub-districts and village mobilized participation to maintain the dynamics of regional conflict if the meeting did not get a meeting point. This was a step taken by the government, the facilitator aspect facilitated the government from the sub-district to get and discuss the problems together that were the basis of the conflict. and as an actor so that this problem had not been resolved until now but this land conflict was lingering until now.